Photopolymerization-Based Synthesis of Uniform Magnetic Hydrogels and Colorimetric Glucose Detection - Mun, Seok Joon (Materials (Basel), 2020)
Magnetic hydrogels have been commonly used in biomedical applications. As magnetite nanoparticles (MNPs) exhibit peroxidase enzyme-like activity, magnetic hydrogels have been actively used as signal transducers for biomedical assays. Droplet microfluidics, which uses photoinitiated polymerization, is a preferred method for the synthesis of magnetic hydrogels. However, light absorption by MNPs makes it difficult to obtain fully polymerized and homogeneous magnetic hydrogels through photoinitiated polymerization. Several methods have been reported to address this issue, but few studies have focused on investigating the light absorption properties of photoinitiators. In this study, we developed a simple method for the synthesis of poly(ethylene glycol) (PEG)-based uniform magnetic hydrogels that exploits the high ultraviolet absorption of a photoinitiator. Additionally, we investigated this effect on shape deformation and structural uniformity of the synthesized magnetic hydrogels. Two different photoinitiators, Darocur 1173 and lithium phenyl (2,4,6–trimethylbenzoyl) phosphinate (LAP), with significantly different UV absorption properties were evaluated based on the synthesis of magnetic hydrogels. The magnetic characteristics of the PEG-stabilized MNPs in hydrogels were investigated with a vibrating sample magnetometer. Finally, the colorimetric detection of hydrogen peroxide and glucose was conducted based on the enzyme-like property of MNPs and repeated several times to observe the catalytic activity of the magnetic hydrogels.